Genetics : From Genes To Genomes - Fischer, Janice A (New york : McGraw-Hill, 2024)
Genetics: From Genes to Genomes represents a new approach to an undergraduate course in genetics. It reflects the way the authors currently view the molecular basis of life. The eighth edition emphasizes both the core concepts of genetics and the cutting-edge discoveries, modern tools, and analytical methods that will keep the science of genetics moving forward.
Includes index.
Keywords: Genetics; Chromosome; Genomics; Mutation; Cancer Genetics